Benign skin tumors in older persons: a population-based study - Nelli Leskelä; Laura Huilaja; Jari Jokelainen; Suvi-Päivikki Sinikumpu (BMC Geriatrics)
Abstract Background Benign skin tumors become more common with advanced age. However, little is known about the etiology of these common lesions. Our objectives were to evaluate the risk factors for seborrheic keratosis, lentigo solaris, cherry angiomas and melanocytic nevi in an elderly population. Our candidate predisposing factors were sex, age, Fitzpatrick skin type, history of outdoor work, life style factors and anthropometric measurements and laboratory tests. Methods In this retrospective cross-sectional study of a large, well-documented cohort, a total body skin examination (TBSE) was performed by dermatologists. The information gathered was augmented with self-reported data. The associations between benign skin tumors and the risk factors analysed with the Chi square test, Fischer exact test and analysis of variance as appropriate. Results The study included 552 participants aged between 70 and 93 years. According to the TBSE, benign skin tumors were present in up to 78.7% in certain subsets of participants. Seborrheic keratosis was the most common lesion type, and 15.6% of all cases had > 50 lesions. Seborrheic keratosis were more common in males (p < 0.05), while lentigo solaris and cherry angiomas were more common in females (p < 0.05). A history of outdoor working associated with higher number of lentigo solaris and seborrheic keratosis lesions (p < 0.05). There was an association between lower glycated haemoglobin levels and the presence of multiple cherry angiomas (p < 0.05). Female subjects with multiple cherry angiomas had higher levels of high-density cholesterol and lower triglyceride values than in those with fewer cherry angiomas (p < 0.05 for both). In males, lower mean haemoglobin levels were associated with multiple cherry angiomas (p < 0.05). Conclusions We found sex differences and several new possible etiological factors behind benign skin tumors which, despite being common, remain poorly characterized.